WINO, CZOSNEK I HANIEBNA ŚMIERĆ. OBRAZ JERZEGO II RAKOCEGO W LITERATURZE POLSKIEJ XVII WIEKU - Tapolcai, László (Prace Polonistyczne, 2021)
The article examines the image of George II Rákóczi, Prince of Transylvania, who led an unsuccessful armed invasion of the Commonwealth in 1657, in the Polish literature of the 17th century. Although somewhat stereotypical, the image created by Rákóczi’s contemporaries was richer than the one created in the following centuries because either the writers knew Rákóczi personally or they were dignitaries, officials, or soldiers who participated in the same events as he did. Literary texts that refer to Rákóczi can be divided chronologically into three groups, the first includes texts written before Rákóczi’s military invasion of the Commonwealth, the second group covers texts written during the invasion, and the third one – texts written after Rákóczi’s defeat (and his later death). This study also addresses some issues related to individual and collective memory as well as the symbols used back then in the portrayals of George II Rákóczi.